VISUAL STORYTELLING TECHNIQUES IN TRADITIONAL AND CONTEMPORARY PAINTING - Porwal, Tina; Neha; Rani, Poonam; Somatkar, Avinash; K, Keerthika; Patil, Balkrishna K (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Painting has also been a core purpose of visual storytelling since it allows one to express cultural materials, beliefs, and human experiences in a visual form. This paper analyses the changes in the methods of visual storytelling in both traditional and contemporary painting along with the development of the way narrative organization, symbolism, material activities and interaction with the viewer has been changing over the recent decades. Traditional painting is examined as a form of narrative based on these characteristics of sharing of iconography, linear or cyclical storytelling and culturally fixed meanings through which stories are interpreted. Contemporary painting, in contrast, has been approached as an open-ended narration practice, which is fragmented, conceptually rich, highly-mediated, and participatorily interpreted. The study is conducted through the lens of a qualitative and comparative analysis based on the narrative theory, visual semiotics, and art-historical analysis to identify the preservation and the breakage of the conventional and modern methods of visual storytelling. The evidence shows that even though modern painting has broken the ties with organization and clarity of storytelling, it still possesses the basic instincts of storytelling in symbolic articulation, emotional appeal, and physical arrangement. The transformation in collective narratives into the subjective and critical storytelling is an indication of wider social, cultural, and philosophical transformation that has attempted to influence the visual culture.